Path Analysis of Blood Glucose Determinant on Diabetes Mellitus Patients through Intervening Variables of Medication Adherence (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
The prevalence of DM patients in Indonesia in 2013 has increased compared to 2007. The non- adherence of patients in undergoing treatment therapy is one of the drug therapy problems (DTP) that needs special attention. The purpose of the study was to obtain the results of an analysis of direct and indirect relationships related to knowledge, attitudes, family support, and adherence to taking medication for blood glucose levels in patients with DM of type II. Research with correlation analytic research design, with a population of all DM patients of type II with outpatient care in the Sleman region, DIY, were 530 people. The sample was determined by the proportionate stratified random sampling technique of 119 people. The independent variables include knowledge, attitude, family support, while the dependent variable is blood glucose levels in patients with DM of type II and the intervening variable is adherence with taking medication. This study uses path analysis techniques. The results of this study draw conclusions, knowledge, attitudes, family support and medication adherence to DM patients with directly influence blood glucose levels. Apart from knowledge, attitudes and family support through adherence to taking drugs indirectly affect blood glucose levels.